Total quality in information systems and technology - Woodall, Jack; Rebuck, Deborah K.;Voehl, Fank (Malaysia : Synergy Book International, 1997)
This work offers insights into melding business and technological operations in order to best serve the interests of the company and its customers. It explains how information technology works in a typical company and how it should work in the ideal company.
1. Harnessing the Power of Information Technology Through Total Quality: An Overview of Technology, Quality, and Information -- 2. Understanding the Information Technology Organization -- 3. Role of Information Technology -- 4. Overview of Total Quality -- 5. House of Quality -- 6. Strategy Management and Quality Planning -- 7. Project Teams and Methodologies -- 8. "How-To" Techniques and Tools -- 9. Electronic Data Interchange -- 10. Horror Stories and How to Avoid Them.
Includes bibliographical references and index.
Keywords: INFORMATION TECHNOLOGY -- MANAGEMENT